Dampak Ekonomi Program Simpan Pinjam Kelompok Perempuan (SPKP) di Kecamatan Kundur Utara - Umi Nur Aqidah; Fitri Kurnianingsih; Ramadhani Setiawan (Faculty of Social and Political Science Universitas Maritim Raja Ali Haji, Indonesia, 2023)
Implementation of a policy in the state is the main thing in the administration of the state. Where is the wrong policy carried out by the government, namely the Women's Group Savings and Loans Program (SPKP) is a poverty alleviation program targeted at women managed by the Activity Management Unit (UPK) in the form of a revolving fund in access to capital. The purpose of this study was to determine the economic impact of the SPKP program in Kundur Utara District. This research uses a qualitative descriptive approach. The dimensions used according to Thomay R. Dye (Agustino 2016:183). The results of this study can be seen from the research indicators, namely 1) the impact on targets or the environment. 2) impact on other groups. 3) impact on the future. 4) impact on direct costs. 5) the impact of indirect costs. The conclusion is that the program (SPKP) implemented by the people of North Kundur District has been running optimally.